Body mass index association with survival in severe aortic stenosis patients undergoing transcatheter aortic valve replacement. Issue 1 (30th December 2015) - Koifman, Edward; Kiramijyan, Sarkis; Negi, Smita I.; Didier, Romain; Escarcega, Ricardo O.; Minha, Sa'ar; Gai, Jiaxing; Torguson, Rebecca; Okubagzi, Petros; Ben‐Dor, Itsik; Satler, Lowell F.; Pichard, Augusto D.; et al.
Abstract : Background: Conflicting results have been reported regarding impact of body mass index (BMI) on outcome of transcatheter aortic valve replacement (TAVR) patients. This study evaluates the impact of BMI on 1 year mortality in patients undergoing TAVR via the transfemoral (TF) access. Methods: Aortic stenosis (AS) patients undergoing TAVR via a TF access between May 2007 and December 2014 were categorized to 4 groups by BMI: low (<20), normal (20–24.9), overweight (25–30), and obese (>30). Baseline parameters were compared, and multivariate Cox proportional hazard regression models were generated to assess outcome differences. Results: Among 491 severe AS TAVR patients, 43 had low BMI, 148 had normal BMI, 162 were overweight, and 138 were obese. Obese patients were younger with lower Society of Thoracic Surgeons scores and higher rates of preserved ejection fraction and diabetes. There was a higher rate of women in the BMI extremes. Aortic valve area was higher among obese patients; however, the indexed area was inversely correlated with BMI. Vascular complications and transfusions were more common in the low‐BMI group, while acute kidney injury was more common in obese patients. All‐cause mortality at 1 year was higher in the low‐BMI group (log‐rank p  = 0.003) with no significant difference among normal and above‐normal BMI patients. In a multivariate model, BMI <20 kg/m 2 was an independent predictor of mortality (HR = 2.45, p  = 0.01). Conclusions: BMI <20 kg/m 2 should be considered a frailty marker during the screening process of severe AS TAVR patients as it is associated with higher mortality, while obesity confers similar mortality risk as normal weight. © 2015 Wiley Periodicals, Inc.